RENEWED ISLAMIC MOVEMENT IN THE PRESS: Case Study of “Ruangan Agama” Rubric in Indonesia Raya Newspaper (1949-1955) (State Islamic University (UIN) of Sunan Ampel Surabaya, 2024)
The era of Liberal Democracy (1950-1959) was a period of political dynamics in which Islamic political parties had a significant role at the time, such as the Masjumi Party and the Nahdlatul Ulama Party. However, in addition to political parties, newspaper is another medium used to promote Islam as a way of life. This article analyzes the column “Ruangan Agama” in the Indonesia Raya newspaper published between 1949 to 1959 in promoting Islam to the public. It is a non-partisan newspaper and not the official media of any party as well. The method used is qualitative and historical approach to get a comprehensive and complete picture of Islamic thought at that time. The findings illustrate that the rubric of the